Basic Ontology and the Ontology of the Phenomenological Life World: A Proposal - Christiaens, Wim (Foundations of Science, 2006)
The condition of explicit theoretically discursive cognitive performance, as it culminates in scientific activity, is, I claim, the life world. I contrast life world and scientific world and argue that the latter arises from the first and that contrary to the prevailing views the scientific world (actually, worlds, since the classical world is substantially different from the quantum world) finds its completion in the life world and not the other way around. In other words: the closure we used to search in a complete and comprehensive scientific description of all aspects of experience by referring it back to underlying atoms, genes and other scientific objects and the covering laws ruling them, should be sought in a reintegrating and occasionally dissolving of the abstract scientific model in the self-organizational fluidity and superposition-like indeterminateness and non-locality of the life world: We have to acknowledge the indeterminate as a positive phenomenon (Merleau-Ponty in his The Phenomenology of Perception).
Keywords: metaphysics; ontology; phenomenology; process ontology